2021
DOI: 10.1080/09297049.2021.1960959
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of early language abilities in children with sex chromosome trisomy (XXY, XXX, XYY) aged 1–6 years

Abstract: Children with sex chromosome trisomy (SCT) are at increased risk for developing language difficulties. Earlier studies have reported that as many as 70-80% of individuals with SCT show some form of language difficulties. Language develops rapidly in the first years of life; knowledge about language development at an early age is needed. The present study aims to identify the language abilities of young children with SCT across multiple language domains and to identify the percentage of children that, according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Children with SCTs show a higher incidence of language delays and impairments [27][28][29][30], and their neuropsychological profile is similar to that of children with DLD (i.e., a significant impairment in verbal skills, with general intelligence usually in the normal range, but with the mean slightly shifted to the left). No significant differences among the three SCT karyotypes were found in the first stages of language development [21,31], though some differences in their profiles could emerge later. For instance, Lee et al [32] suggested that an additional X chromosome (as in triple X syndrome and Klinefelter syndrome) might have a greater effect on structural language abilities, whereas an additional Y (as in Jacobs syndrome) might have a higher impact on pragmatics.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Children with SCTs show a higher incidence of language delays and impairments [27][28][29][30], and their neuropsychological profile is similar to that of children with DLD (i.e., a significant impairment in verbal skills, with general intelligence usually in the normal range, but with the mean slightly shifted to the left). No significant differences among the three SCT karyotypes were found in the first stages of language development [21,31], though some differences in their profiles could emerge later. For instance, Lee et al [32] suggested that an additional X chromosome (as in triple X syndrome and Klinefelter syndrome) might have a greater effect on structural language abilities, whereas an additional Y (as in Jacobs syndrome) might have a higher impact on pragmatics.…”
Section: Introductionmentioning
confidence: 76%
“…Moreover, during a play session in interaction with a parent, these children produced a significantly lower proportion of verbal utterances, and a significantly higher number of pointing gestures than TD children [30]. As Urbanus et al [21] reported in their recent cross-sectional study on 103 children ranging in age from one to six years, the linguistic performance of individuals with SCTs showed large deviations from the control group on nearly all language domains, and the number of children who experience linguistic problems increased with age. Therefore, monitoring language development from the earliest stages of nonverbal communication is fundamental to identifying children at risk, and intervening when needed [21].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations